1997
DOI: 10.1108/03068299710161269
|View full text |Cite
|
Sign up to set email alerts
|

Valuation of gains and losses, fairness and negotiation outcomes

Abstract: Reports the results of two experimental tests of the extent to which the large disparity between people’s valuation of gains and losses, and related fairness determinations, are used in judging the acceptability of alternative negotiating or conflict resolution proposals. Participants acted as arbitrators and selected their preferred resolution of conflicts, involving either the division of gains or sharing responsibility for losses. Different cases were presented in which one or the other party incurred varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…When psychologists have examined peoples' attitudes, there is little doubt that the latter is considered to be the fair outcome. For example, Borges and Knetsch (1997) asked subjects what would be a fair way to share 10 dollars between two people, given that the ten dollars had been generated by an investment of 2 dollars by one of them. The vast majority indicated that the 6 : 4 split would be most fair.…”
Section: Fairnessmentioning
confidence: 99%
“…When psychologists have examined peoples' attitudes, there is little doubt that the latter is considered to be the fair outcome. For example, Borges and Knetsch (1997) asked subjects what would be a fair way to share 10 dollars between two people, given that the ten dollars had been generated by an investment of 2 dollars by one of them. The vast majority indicated that the 6 : 4 split would be most fair.…”
Section: Fairnessmentioning
confidence: 99%
“…Kahneman et al 1991, Borges andKnetsch 1997). Psychological evidence on loss aversion suggests that we should be more reluctant to pay a fee to sanction nasty actions, than to miss an opportunity to profit at somebody else's expense.…”
mentioning
confidence: 99%
“…But it is not obvious that positive and negative reciprocity are governed by the same psychological mechanisms. It is well known that the perception of gains and losses is biased by framing effects, and that missed opportunities are processed differently from directly incurred costs (e.g., Borges & Knetsch 1997;Kahneman et al 1991). Psychological evidence on loss aversion suggests that we should be more reluctant to pay a fee to sanction nasty actions, than to miss an opportunity to profit at somebody else's expense.…”
Section: Concluding Remarks: Reciprocity Without Costly Punishmentmentioning
confidence: 99%